2021
DOI: 10.1097/md.0000000000026058
|View full text |Cite
|
Sign up to set email alerts
|

Plasma D-dimer and FDP are promising biomarkers to predict perioperative fibrinolysis and bleeding following primary total joint arthroplasty

Abstract: Perioperative bleeding is associated with postoperative hyperfibrinolysis caused by surgical trauma in the setting of total hip and knee arthroplasty (THA/ TKA). The study aimed to clarify the dynamics of postoperative fibrinolytic activity and the values of fibrin degeneration products and thromboelastography (TEG) to guide precisive antifibrinolytic therapy. Forty three patients undergoing primary unilateral THAs and 40 TKAs were included to the prospective observational cohort study. Venous blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…D-dimers are thus an effective and practical routine marker for early prediction of acute fibrinolytic activity and occurrence of a hemorrhagic complication. 33 In this context, we propose that the increased D-dimer levels originate during ongoing fibrinolysis from fibrin deposits in vascular and tissue lesions, 30 which aligns with the higher tPA concentration. The concentration of plasmin–antiplasmin complexes, which are passive markers of plasmin formation, was also increased.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…D-dimers are thus an effective and practical routine marker for early prediction of acute fibrinolytic activity and occurrence of a hemorrhagic complication. 33 In this context, we propose that the increased D-dimer levels originate during ongoing fibrinolysis from fibrin deposits in vascular and tissue lesions, 30 which aligns with the higher tPA concentration. The concentration of plasmin–antiplasmin complexes, which are passive markers of plasmin formation, was also increased.…”
Section: Discussionmentioning
confidence: 92%
“…7,27,28 Elevated D-dimer levels often suggest ongoing fibrinolysis. 29,30 Balaguer et al 8 demonstrated in cardiopulmonary bypass patients that blocking bradykinin B2 receptor led to a reduction in fibrinolytic capacity comparable to ε-aminocaproic acid. However, D-dimer formation was specifically decreased only by the latter, likely attributed to its direct impact on plasminogen fibrin-binding function.…”
Section: Discussionmentioning
confidence: 99%
“…The Strengthening the Reporting of Observational studies in Epidemiology (STROBE) cross-sectional reporting guidelines were used. 17…”
Section: Study Design and Ethical Considerationsmentioning
confidence: 99%
“…Currently, there is a lack of other convenient and effective serological indicators for assessing RA activity. [1] Fibrinogen degradation products (FDP) and D -dimer are products of the activated fibrinolytic system that are closely associated with thrombotic diseases, and high FDP and D -dimer levels are also observed in patients with malignant diseases, [2,3] pregnancy, [4] prosthetic replacement arthroplasty, [5] novel coronavirus pneumonia, [6] and sepsis. [7] Cerebral and myocardial infarctions are common thrombotic disorders associated with atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%